Improvement cues of lesion absorption using the adjuvant therapy of traditional Chinese medicine Qinbudan tablet for retreatment pulmonary tuberculosis with standard anti-tuberculosis regimen - Shao-Yan Zhang; Ji-You Fu; Xiao-Yan Guo; Ding-Zhong Wu; Tong Zhang; Cui Li; Lei Qiu; Chang-Rong Shao; He-Ping Xiao; Nai-Hui Chu; Qun-Yi Deng; Xia Zhang; et al. (Infectious Diseases of Poverty, 2020)
Abstract Background China is the second highest pulmonary tuberculosis (PTB) burden country worldwide. However, retreatment of PTB has often developed resistance to at least one of the four first-line anti-TB drugs. The cure rate (approximately 50.0–73.3%) and management of retreatment of PTB in China needs to be improved. Qinbudan decoction has been widely used to treat PTB in China since the 1960s. Previously clinical studies have shown that the Qinbudan tablet (QBDT) promoted sputum-culture negative conversion and lesion absorption. However, powerful evidence from a randomized controlled clinical trial is lacking. Therefore, the aim of this study was to compare the efficacy and safety of QBDT as an adjunct therapy for retreatment of PTB. Methods We conducted a multicenter, randomized, double-blind, placebo-controlled clinical trial in China. People diagnosed with PTB were enrolled who received previous anti-TB treatment from April 2011 to March 2013. The treatment group received an anti-TB regimen and QBDT, and the control group was administered an anti-TB regimen plus placebo. Anti-TB treatment options included isoniazid, rifampicin, pyrazinamide, ethambutol, streptomycin for 2 months (2HRZES), followed by isoniazid, rifampicin, ethambutol for 6 months (6HRE), daily for 8 months. Primary outcome was sputum-culture conversion using the MGIT 960 liquid medium method. Secondary outcomes included lung lesion absorption and cavity closure. Adverse events and reactions were observed after treatment. A structured questionnaire was used to record demographic information and clinical symptoms of all subjects. Data analysis was performed by SPSS 25.0 software in the full analysis set (FAS) population. Results One hundred eighty-one cases of retreatment PTB were randomly divided into two groups: the placebo group (88 cases) and the QBDT group (93 cases). A total of 166 patients completed the trial and 15 patients lost to follow-up. The culture conversion rate of the QBDT group and placebo group did not show a noticeable improvement by using the covariate sites to correct the rate differences (79.6% vs 69.3%; rate difference = 0.10, 95% confidence interval (CI): - 0.02–0.23; F = 2.48, P = 0.12) after treatment. A significant 16.6% increase in lesion absorption was observed in the QBDT group when compared with the placebo group (67.7% vs 51.1%; rate difference = 0.17, 95% CI: 0.02–0.31; χ 2 = 5.56, P = 0.02). The intervention and placebo group did not differ in terms of cavity closure (25.5% vs 21.1%; rate difference = 0.04, 95% CI: - 0.21–0.12; χ 2 = 0.27, P = 0.60). Two patients who received chemotherapy and combined QBDT reported pruritus/nausea and vomiting. Conclusions No significant improvement in culture conversion was observed for retreatment PTB with traditional Chinese medicine plus standard anti-TB regimen. However, QBDT as an adjunct therapy significantly promoted lesion absorption, thereby reducing lung injury due to Mycobacterium tuberculosis infection. Trial registration This trial is registered at ClinicalTrials.gov, NCT02313610 .